Peran Pemerintah Daerah dan Pemberdayaan Masyarakat dalam penyelenggaraaan Event Daerah Di Desa Baloli Kabupaten Luwu Utara - Andi Hasbi (Institut Pemerintahan Dalam Negeri, 2023)
Abstract The Role of Local Government and the Community in Involving Village Officials and the Local Government, Academics, and Society in Supporting the Cultural Event